Assessing the Cause of Food Waste Behavior of Consumers at Food Courts in Banyumas, Indonesia: Intention to Reduce Food Waste as a Mediator - Rahman, Zulham; Romadlon, Fauzan (Journal of Community Based Environmental Engineering and Management, 2025)
Food waste is a global hindrance to sustainable food systems. In Indonesia, a lot of food suitable for consumption is wasted annually. In 2023, Banyumas Regency was dominated by the most significant portion of food waste, with a daily volume of 541.80 tons. Food waste comes from hotels, restaurants, and trade sectors, such as food court areas. Therefore, this study aims to analyze factors influencing consumers' food waste behavior at food courts in Banyumas Regency. The method used was quantitative, with 410 respondents, and this research employed structural equation modeling-partial least squares (SEM-PLS). The factors influencing food waste generation include food choice, food literacy, social influence and normative behavior, food ordering routine, intention to reduce food waste, and food waste behavior. The results show that food choice and food literacy have a significant relationship with intention to reduce food waste (IR), and IR has a significant relationship with food waste behavior (FWB). The result also shows that IR mediates the relationship between Food choice (FC) and FWB, and IR mediates the relationship between food literacy (FL) and FWB. Food choice and literacy play a significant role in shaping the intention to reduce food waste. This contributes to the literature on avoiding food waste behavior by emphasizing the importance of cognitive (food knowledge) and affective (food preferences) influences on changing more sustainable consumption behavior. The food court manager can develop visual campaigns in the area, train consumers, and provide flexible food portions that suit customer needs to minimize food waste.